Dinamika Peradaban Islam: Kajian Sejarah Pemikiran, Politik dan Budaya - Suci Urmilawati; Zainuddin Syarif (Kartika: Jurnal Studi Keislaman, 2026)
Islamic civilization is the product of dynamic interaction between the dimensions of thought, politics, and culture throughout its history. This article aims to analyze the interrelation of these three pillars in shaping the character of Islamic civilization, from the classical to the contemporary era. Methodologically, this research uses a historical-analytical approach and is conducted through a literature study, tracing primary and secondary sources related to the development of theological-philosophical thought, the transformation of political configurations from the era of the Khulafa’ al-Rashidun to the modern nation-state, as well as cultural dynamics that reflect processes of acculturation. The findings indicate that the progress of Islamic civilization occurred when there was positive synergy: creative-rational thought, a political structure supportive of intellectual freedom, and a cosmopolitan culture. Conversely, intellectual stagnation and political authoritarianism were directly proportional to cultural decline. The article concludes that the revival of contemporary Islamic civilization requires an integrative reconstruction of these three dimensions, which can only be achieved through an interdisciplinary and contextual approach to formulate a synthesis relevant to the modern age